HUBUNGAN RUMAH SEHAT DENGAN KEJADIAN TB PARU DI KECAMATAN PALENGAAN KABUPATEN PAMEKASAN - Andri Setiya Wahyudi (Wiraraja Medika : Jurnal Kesehatan, 2013)
Housing condition is one factor that determines the state of hygiene and environmental sanitation. Houses construction and the environment that do not meet health requirements are risk factors for the source of diseases transmission, one of them is pulmonary tuberculosis. This research was conducted to determine the relation of healthy house with the incidence of tuberculosis in Palengaan, Pamekasan. This was an observational study, based on its time; it was a case control study. Data analysis used Chi square test with 0.05 of α. This study assessed healthy house by using the observation sheet in the technical guidelines of healthy house assessment by the Directorate General of Communicable Diseases Eradication and Environmental Health in 2002.Variables used which were the result of house health assessment include (a) house component, (b) sanitary facilities, and (c) occupant behavior, individual characteristics include a) age, (b) sex, and (c) education, and residential density. Based on the study results, house health assessment’s result associated with the incidence of pulmonary TB, chi square test p = 0.000, OR = 35.10 and in 3 groups of house health assessment can be seen that the behavior of occupants associated with the incidence of pulmonary TB , chisquare test p=0,001; OR=8,233. The conclusion that can be drawn is healthy house can reduce the risk of pulmonary TB incidence, esspecially poor behavior of occupants can increase the risk of pulmonary TB incidence.Key words: healthy house, behavior, residential density and pulmonary, tuberculosis